2018
DOI: 10.1080/10253890.2018.1459557
|View full text |Cite
|
Sign up to set email alerts
|

Timing matters: the interval between acute stressors within chronic mild stress modifies behavioral and physiologic stress responses in male rats

Abstract: Chronic mild stress can lead to negative health outcomes. Frequency, duration, and intensity of acute stressors can affect health-related processes. We tested whether the temporal pattern of daily acute stressors (clustered or dispersed across the day) affects depression-related physiology. We used a rodent model to keep stressor frequency, duration, and intensity constant, and experimentally manipulated the temporal pattern of acute stressors delivered during the active phase of the day. Adult male Sprague-Da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 49 publications
1
12
0
Order By: Relevance
“…The CMS model also resulted in lower body weight gain in the experimental rats than the control rats. Cavigelli et al demonstrated that four weeks of CMS reduced the body weight of rats [20]. Another study reported that six weeks of CMS significantly reduced body weight, and fluoxetine antidepressant treatment improved depressive-like behaviors without causing body weight gain [21].…”
Section: Discussionmentioning
confidence: 99%
“…The CMS model also resulted in lower body weight gain in the experimental rats than the control rats. Cavigelli et al demonstrated that four weeks of CMS reduced the body weight of rats [20]. Another study reported that six weeks of CMS significantly reduced body weight, and fluoxetine antidepressant treatment improved depressive-like behaviors without causing body weight gain [21].…”
Section: Discussionmentioning
confidence: 99%
“…As noted in Tables 2 and 3, the majority of cytokine levels increased between the 3 h and 6 h time points, even for the saline treated controls. Animals in the present study received multiple bouts of restraint and blood sample collection within 6 h, potentially inducing stress that may exacerbate cytokine response (Johnson et al, 2002; Cavigelli et al, 2018). Moreover, metabolic chambers, such as the CLAMS, have been associated with stress responses in rodents and may have contributed to the relatively high baseline cytokine levels in the saline group (Kalliokoski et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…These changes do not impact the academic content of the article. and populations (Tractenberg et al, 2016;Bonapersona et al, 2019;Shields et al, 2017;Loi et al, 2017;Cavigelli et al, 2018), it is critically important to optimize experimental designs to address the specific experimental questions.…”
Section: The Heterogeneity Of "Stress"mentioning
confidence: 99%